Postural sway in young female artistic and acrobatic gymnasts according to training experience and anthropometric characteristics - Opala-Berdzik, A.; Glowacka, M.; Juras, G. (BMC Sports Science, Medicine and Rehabilitation, 2021)
Background: Gymnastics training enhances the development of postural control in children and adolescents. In competitive gymnastics, the training regimen is specific to the given gymnastic discipline and is usually followed from the early years of practicing. This study aimed to determine whether postural steadiness differed between young gymnasts practicing two distinct disciplines, and whether it was related to the duration of their training experience, age, and their anthropometric characteristics. Methods: Thirty 10-13-year-old females (ten artistic gymnasts, ten acrobatic gymnasts (training as "tops"), and ten non-athletes ? were examined during 60-s quiet standing trials on a force platform with the eyes open and closed. Their postural sway was represented by directional components of centre of foot pressure mean velocity. Mann-Whitney U, Wilcoxon and Spearman`s tests were used for analyses. Results: Anterior-posterior and medial-lateral centre of foot pressure mean velocities were not different between the artistic and acrobatic gymnasts (p > 0.05). In the artistic gymnasts, the duration of training experience, age, body height, body mass, and maturity offset were negatively correlated with the anterior-posterior centre of foot pressure mean velocity under eyes-open conditions. The acrobatic gymnasts` body mass and BMI percentiles were negatively correlated with their anterior-posterior and medial-lateral centre of foot pressure mean velocities under both visual conditions (r ranged from - 0.64 to - 0.93; p < 0.05). The non-athletes` centre of foot pressure mean velocities were non-significantly correlated with their age and anthropometric measures under both visual conditions (p > 0.05). Conclusions: The artistic gymnasts` longer training experience, greater age, body height, body mass, and biological maturity were associated with better anterior-posterior postural steadiness when vision was available; the acrobatic gymnasts` greater body mass and BMI percentiles were associated with better overall postural steadiness regardless of visual conditions. Relationships were observed between postural steadiness and discipline-specific training experience and anthropometric characteristics; however, causes and effects were not proven.